Characterization of the novel HLA‐DRB1*04:326 allele by next generation sequencing. (20th July 2021) - Jacob, Valentine; Usureau, Cédric; Villemonteix, Juliette; Desoutter, Judith; Guillaume, Nicolas
Abstract : HLA‐DRB1*04:326 differs from HLA‐DRB1*04:01:01 by one nucleotide substitution in codon 23 in exon 2.